Value of maternal tactile method in detecting fever among under five years children during the COVID-19 era - Ali Adel Shareef; Nuha Hachim Alasaf; Marab Younis Abdullah Al-Fathy (Hygeia Press di Corridori Marinella, 2024)
Objectives: The ability of mothers to accurately predict the presence of fever in their children using the tactile method is still controversial. This study evaluated the accuracy of Iraqi mothers' tactile fever detection in children under 5 during COVID-19 pandemic. Materials and methods: Interviews were conducted with 200 mothers whose children were under the age of 5 years and who assumed they had fever. Each mother was then asked to touch her child's body for fever evaluation, while an investigator observed them, recorded their responses, and documented the places of palpation. Thereafter, the investigator determined the child's temperature using a non-contact temple thermometer (NCTT). Statistical analysis was conducted to compare the maternal tactile approach to NCTT and single site to multiple site palpation in terms of sensitivity, specificity, and predictive values. Results: The prevalence of fever in the study sample was 72%, as 144 of the 200 children involved were confirmed to have fever by NCTT. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the maternal tactile method were 96.5%, 62.5%, 86.9%, and 87.5%, respectively. Multiple child body sites were palpated by 42.5% of mothers, whereas 57.5% palpated a single site, with the forehead being the most common palpated site (31%). Multiple site palpation had a significantly lower incorrect temperature assessment rate than single site palpation (3.5% vs. 27%, p = 0.00001). Additionally, the accuracy increased significantly when the mother palpated multiple sites (96.5% vs. 73%). Conclusion: The findings of this study suggest that mothers' use of tactile assessment is an effective screening tool when assessing their children's fever; however, mothers' fears can reduce the accuracy of this method, whereas instructing the mother to palpate multiple body parts can increase its reliability.